4ln(x)+6=0

Simple and best practice solution for 4ln(x)+6=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4ln(x)+6=0 equation:


Simplifying
4ln(x) + 6 = 0

Multiply ln * x
4lnx + 6 = 0

Reorder the terms:
6 + 4lnx = 0

Solving
6 + 4lnx = 0

Solving for variable 'l'.

Move all terms containing l to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + 4lnx = 0 + -6

Combine like terms: 6 + -6 = 0
0 + 4lnx = 0 + -6
4lnx = 0 + -6

Combine like terms: 0 + -6 = -6
4lnx = -6

Divide each side by '4nx'.
l = -1.5n-1x-1

Simplifying
l = -1.5n-1x-1

See similar equations:

| 6m+m+4(2m+1-m)=8 | | 2r+3=0 | | -3h-7h-20h+17h=-13 | | 27=5y-3 | | 3p(p-2)=p-2 | | 15w^3+20w^2= | | 2y+12=-5y+19 | | 5n-34=n+10 | | 4(2y+5)=3(2y+13) | | -2j+12j+10j+12j+18=-6 | | 0.7*0=2.8 | | 21x+2+14x+2=180 | | m=20a(4)+8c(2) | | -5(3x-5)=-35-5x | | 3x+9=8y+39 | | 34n+n+5n-32n+2n=40 | | 10x+5=6x-1 | | 14x+5x=76 | | .25x+2=-12.5x-5 | | -15z+3z+-13z+17z+7z=20 | | 9x+1=2(4x-2)+5 | | -4x+14=-3x-7 | | 16x+18-15=3 | | 4(3m+2)=-40 | | 5=5-(2x-4) | | a+2a+4(2a)=44 | | 15d-14d-d+d+2=19 | | 12x+5-9=-4 | | 2x-5(x-2)=-7+3x-13 | | -.5x+3=4-.25x | | 8(x+4)-8=30-6x-6+14x | | 1x+5-3=2 |

Equations solver categories